"BUKA MATA, BUKA HATI” PELATIHAN KEWIRAUSAHAAN YANG TERINTEGRASI, KOMPREHENSIF, DAN BERWAWASAN LINGKUNGAN (BAGI WANITA BUDDHIS PROPINSI SUMATERA SELATAN) - Dewi Sri; Maria F.S.Sulistyawati; Tiurma; Feby Astrid Kesaulia; Johan Gunady Ony (Jurnal Abdimas Musi Charitas, 2018)
Women have a very large role in the family. Today the role of women is not just a career, childeducator, caring for her husband and home, but also must play a role in managing familyfinances. The higher awareness of quality of life leads women to become more involved infinancial management and even become the second breadwinner subject after the husband. Thistraining is an early stage training that provides participants with basic knowledge about theimportance of spiritual in supporting work performance, knowledge about health,entrepreneurial motivation, understanding of finance, and skills in processing fabric waste.